Clathrin Is Important for Virulence Factors Delivery in the Necrotrophic Fungus Botrytis cinerea - Souibgui, Eytham; Bruel, Christophe; Choquer, Mathias; de Vallée, Amélie; Dieryckx, Cindy; Dupuy, Jean William; Latorse, Marie-Pascale; Rascle, Christine; Poussereau, Nathalie (Frontiers in Plant Science, 2021)
Fungi are the most prevalent plant pathogens, causing annually important damages. To infect and colonize their hosts, they secrete effectors including hydrolytic enzymes able to kill and macerate plant tissues. These secreted proteins are transported from the Endoplasmic Reticulum and the Gol-gi apparatus to the extracellular space through intracellular vesicles. In pathogenic fungi, intracellular vesicles were described but their biogenesis and their role in virulence remain unclear. In this study, we report the essential role of clathrin heavy chain (CHC) in the pathogenicity of Botrytis cinerea, the agent of grey mold disease. To investigate the importance of this protein involved in coat vesi-cles formation in eukaryotic cells, a T-DNA insertional mutant reduced in the expression of the CHC-encoding gene, and a mutant expressing a dominant-negative form of CHC were studied. Both mutants were strongly affected in pathogenicity. Characterization of the mutants revealed altered infection cushions and an important defect in protein secretion. This study demonstrates the essential role of clathrin in the infectious process of a plant pathogenic fungus and more particularly its role in virulence factors delivery.